PARTISIPASI MASYARAKAT DALAM PENGELOLAAN OBJEK WISATA ISTANO BASA PAGARUYUANG DI KECAMATAN TANJUNG EMAS KABUPATEN TANAH DATAR - Murni, Megi Efri (STKIP PGRI Sumbar, 2014)
Indonesia is a beautiful country. It can be utilized by all of Indonesia society as a tourismobject. Beside that Indonesia also has a difference culture among regions, which are the culturebecame the tourism place for people. Thr porpuse of this research is to get a data and informationabout people participate in tourism object managemen Istano Basa Pagaruyung KecamatanTanjung Emas Kabupaten Tanah Datar.The type of research is kalitatif, the informan of research taken from poposive samplingtechnik ques. With subject or aresponden of tourism research department, camat kecamatantanjung emas and people who live around istano basa pagaruyung. The data collected throughstructure interview of observation and documentation. The data which are collected is aboutcitizen participation in the managemen of the managemen of the tourism object in term ofsafety, cleanliness, hospitality, and accommodation.the results of study found: (1) participation of people in tourism management clealinessIstano Basa Pagaruyung is good enough, all the looks of Istano basa alkaline environmentclean, in addition to the participation of the community in an existing object withou Istano basadirect officers keeping it clean (2) participation of people in tourism management security ofattraction Istano basa pagaruyung good, seen from the comfort felt by the visitor in, and themany visitors who come to the attraction. In addition, officers are important in maintaining thesecurity of object Istano bases Pagaruyung. (3) participation people in hospitality friendlyattitude towards visitors already well established, visible from every officer and communitiesaround bases Pagaruyung attraction Istano serve the end if there visiting that require assistanceand imformasi. (4) accommodation in object Istano basa Pagaruyung nothing, and for visitorsthat wish long in Istano basa Pagaruyung could only find accommodation in the city centerbatusangkar.untuk tourism department to further improve security and development AttractionsIatano Pagaruyung Bases, and for attractions manager Istano Basa Pagaruyung to work togetherwith communities to promote and enhance the attractions Istano Pagaruyung Basa.